2015
DOI: 10.5380/rf.v45i4.37454
|View full text |Cite
|
Sign up to set email alerts
|

MODELAGEM DE VARIÁVEIS MORFOLÓGICAS EM MUDAS DE Eucalyptus dunnii

Abstract: ResumoAs variáveis morfológicas de mudas florestais podem ser indicativos de sua qualidade, sendo de grande importância para o sucesso de empreendimentos florestais. Nesse contexto, o objetivo do estudo foi correlacionar as variáveis operacionalmente mensuráveis (diâmetro do colo e altura) com as de mensuração destrutiva (área foliar e comprimento de raiz) de mudas de E. dunnii, de modo a formular equações que forneçam estimativas precisas dessas variáveis. Para isso, avaliou-se 77 mudas com 100 dias de idade.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This parameter is influenced by environmental conditions, population density and nutritional status. When evaluated in the field, the stem diameter is considered a reliable feature, since it is easy to be measured and has high correlation to the seedling survival, thus helping to determine the quality of seedlings (Nicoletti et al, 2015). Rudek et al (2013) and Nicoletti et al (2015) studying Eucalyptus sp., observed that the combination of leaf area and stem diameter was a reliable parameter when determining seedling quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter is influenced by environmental conditions, population density and nutritional status. When evaluated in the field, the stem diameter is considered a reliable feature, since it is easy to be measured and has high correlation to the seedling survival, thus helping to determine the quality of seedlings (Nicoletti et al, 2015). Rudek et al (2013) and Nicoletti et al (2015) studying Eucalyptus sp., observed that the combination of leaf area and stem diameter was a reliable parameter when determining seedling quality.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the most used are plant height and stem diameter. These parameters are easily measured and they can provide reliable data on seedlings strength and functionality (Nicoletti et al, 2015;Santos et al, 2018). The stem diameter is the most analyzed feature to indicate the seedlings survival capacity in the field (D'avila et al, 2011).…”
Section: Introductionmentioning
confidence: 99%